Правові основи реалізації адміністративних повноважень у державній митній справі - Левченко, Світлана Григорівна; Левченко, Светлана Григорьевна; Levchenko, Svitlana G. (My University, 2014)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.07 – адміністративне право і процес; фінансове право; інформаційне право. Дисертацію присвячено науковому дослідженню правових основ реалізації адміністративних повноважень у державній митній справі. Сформульовано поняття адміністративних повноважень у сфері державної митної справи. Здійснено класифікацію адміністративних повноважень у державній митній справі за змістом, способом здійснення, залежно від організаційно-правового рівня адміністративних повноважень суб’єктів реалізації митної справи, функцій, покладених на митні органи, та здійснено поділ адміністративних повноважень на повноваження, які безпосередньо впливають на порядок переміщення товарів та транспортних засобів комерційного призначення через митний кордон України, та допоміжні повноваження, спрямовані на створення умов для реалізації основних. Увагу приділено формам, видам та процедурам реалізації адміністративних повноважень у державній митній справі. Сформульовано поняття взаємодії у державній митній справі та визначено цілі такої взаємодії. Досліджено принципи взаємодії у сфері державної митної справи. На підставі аналізу чинного законодавства України з питань державної митної справи, що стосується адміністративних повноважень у державній митній справі, запропоновано внесення змін до Митного кодексу України щодо призначення та завдань митних органів.

Диссертация на соискание научной степени кандидата юридических наук по специальности 12.00.07 – административное право и процесс; финансовое право; информационное право. Диссертация посвящена научному исследованию правовых основ реализации административных полномочий в государственном таможенном деле. Сформулировано понятие административных полномочий в сфере государственного таможенного дела. Осуществлена классификация административных полномочий в государственном таможенном деле по содержанию, способу осуществления, в зависимости от организационно- правового уровня административных полномочий субъектов реализации таможенного дела, функций, возложенных на таможенные органы, а также осуществлено разделение административных полномочий на полномочия, которые непосредственно влияют на порядок перемещения товаров и транспортных средств коммерческого назначения через таможенную границу Украины, и вспомогательные полномочия, которые направлены на создание условий для реализации основных. Внимание уделено формам, видам и процедурам реализации административных полномочий в государственном таможенном деле. Сформулировано понятие взаимодействия в государственном таможенном деле и определены цели такого взаимодействия. Исследованы принципы взаимодействия в сфере государственного таможенного дела. На основании анализа действующего законодательства Украины по вопросам государственного таможенного дела, касающегося административных полномочий в государственном таможенном деле, предложено внесение изменений в Таможенный кодекс Украины относительно назначения и задач таможенных органов.

Ph.D thesis in Law with a specialization according to 12.00.07 – Administrative Law and Procedure; Financial Law; Information Law.21 The thesis deals with a scientific study of the legal basis of carrying out administrative powers in the state customs affair. It is established that the reorganization of the systems of customs bodies, establishment and liquidation of the Ministry of Revenues and Duties of Ukraine, establishment of the State Fiscal Service and renovation of the legislation of Ukraine as regards the state customs procedures, which core of upgrading is the development and adoption of the new Customs Code aimed at establishment of partnership relations among customs administrations, entities of the external economic activity and individuals have established brand new approaches to the determination of the content, legal nature, properties and classification capabilities of administrative powers in the state customs affair. It was proved that the administrative powers in the state customs affair are one of the special attribute of the customs bodies system and directly impact their actual capacity to exercise the state customs affair, accomplish its purposes and the main tasks in said sphere, which necessitates a deep and multifaceted study and clarification of the content, attributes, properties and classification possibilities of this category of the law. The author formulated a notion of administrative powers in the state customs affair as an aggregate of the rights and liabilities of the customs bodies that are defined by their civil liability areas, application of the customs law and levying duties and taxes, as well as application of other laws and rules concerning import, export, transfer or storage of commodities. Administrative powers pertaining to the state customs affair are classified by their content, methods of administering, depending on the organizational and legal levels of administrative powers of the customs bodies, functions imposed upon the customs bodies in the sphere of the state customs affair; administrative powers are divided into those that directly influence the procedure of transfer of commodities and commercial transport vehicles across the customs border of Ukraine, and the auxiliary powers (aimed at creating conditions for accomplishing the main powers). Significant attention is given to the forms, kinds and procedures to accomplish administrative powers pertaining to the state customs affair. Formulated is the notion of interaction in the state customs affair meant as an activity of the customs bodies and other entities of the customs legal relations that exercise control and adherence to the customs law norms that is regulated by the customs law and agreed according to the objective, time and place. The objectives of interaction in the state customs affair have been defined: the objectives that are directly linked to the measures that counteract violations of the Law of Ukraine pertaining to the customs procedures, and the objectives that provide for optimization of the activities aimed at achieving the objectives of the first kind. Studied are the principles of interaction in the state customs affair: legitimacy; scientific character; planned nature; continuity; main link principle; expedition; efficient an economic use of the possibilities arising between interacting elements; and the proportional liability principle. On the basis of the analysis of the existing legal base of Ukraine pertaining to the state customs affair as reflected in the administrative powers in the sphere of the state customs affair, it is proposed to amend the Customs Code of Ukraine in terms of application and tasks of the customs bodies in the sphere of the state customs affair.
Левченко С. Г. Правові основи реалізації адміністративних повноважень у державній митній справі : автореф. дис. ... канд. юрид. наук : 12.00.07 / С. Г. Левченко; кер. роботи Б. А. Кормич; Нац. ун.-т "Одеська юридична академія". – Одеса, 2014. – 22 с.
Keywords: державна митна справа; адміністративні повноваження; компетенція у державній митній справі; реалізація адміністративних повноважень; правотворчість; правозастосування; адміністративна діяльність; взаємодія; государственное таможенное дело; административные полномочия; компетенция в государственном таможенном деле; реализация административных полномочий; правотворчество; правоприменение; административная деятельность; взаимодействие; state customs affair; administrative powers; competence in the state customs affair; accomplishment of administrative powers; lawmaking; law enforcement; administrative activity; interaction